M.Ilham (10300116154) Pembebasan Bersyarat Kasus Narkotika dalam Upaya Pembinaan Narapidana: Studi Komparasi Mazhab Hanafi dan Hukum Nasional - M. Ilham; Syatar, Abdul (Universitas Islam Negeri Alauddin Makassar, 2023)
Parole is the process of fostering convicts and criminal children outside the Correctional Institution after serving at least 2/3 (two thirds) of their minimum sentence of 9 (nine) months (Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number M.2.PK.04 -10 of 2007) article 1 paragraph 2. The granting of parole is one of the legal means in the context of realizing the goals of the correctional system. The right of inmates to obtain parole is regulated in the provisions of Article 14 letter k of the Correctional Law. Narkoba is an abbreviation of narcotics and drugs/dangerous substances. In addition to narcotics, another term introduced especially the Ministry of Health of the Republic of Indonesia is narcotics which stands for narcotics, psychotropics, and addictive. This type of research is library research. Broadly speaking, the approach used by the authors in this thesis is a sociological, historical, and anthropological approach. The data collection techniques used in obtaining the necessary information related to the problem under study are: Literature Study, is a data collection technique by reading literature books and literatures that can be used as guidelines or data sources in making this thesis. The literature study includes: 1.) Primary data, 2.) Secondary data. The purpose of this study is to analyze analytically how to parole narcotics convicts from both Positive Law and the Hanafi School of Law. Karen has now been shown how the life and fate of convicts in narcotics cases is uncertain, sometimes they are discriminated against by the social community. Become new insights and ideas about how to parole narcotics cases. The results of this study. If no qhoth'I arguments are found either in the Qur'an or in the Hadith whose validity is not in doubt, Imam Abu Hanafiah will determine the law based on Ra'yu. Imam Abu Hanafiah was influenced by legal developments in Kufa which was located far from Mandinah as the city where the Prophet Muhammad lived. So Imam Abu Hanafiah through his legal terms views narcotics as khamr or anything that is categorized as intoxicating and forbidden through the Qiyas approach.